LEADING IN NEPANTLA: THE COMPLEXITY OF SERVING AS A TEACHER AND LEADER IN A TEACHER-LED SCHOOL - De Alba, Adrian (East Carolina University)
Teachers traditionally work in a classroom and have little to no say outside those walls. I engaged a group of four co-practitioner researchers (CPR) from an alternative teacher-led school in a participatory action and activist research (PAAR) project and study. As teachers and leaders, they occupied nepantla - a liminal space between teaching and leading and between their values and district constraints. I analyzed how teachers as leaders developed and implemented a project-based instructional program in an alternative school and the assets and challenges they encountered. In the final data cycle, I conducted an ethnographic study of two teacher leaders as they shared their successes and challenges in operating a teacher-led school focused on shifting the power structure to include students. Using the Community Learning Exchange axioms and protocols (Guajardo et al., 2016), the team crossed boundaries to develop their individual and collective capacity as school leaders. At the intersection between teaching and leading and between district demands and their belief in the power of student-generated curriculum, the teachers as leaders collaborated to leverage student voices amid challenges. The team challenged the traditional hierarchy, elevating teachers as leaders and allowing them to exist in a complex environment in which they experienced freedom and conflict. The findings emerged as a cautionary tale: (1) Teacher leaders in an alternative school without a principal did not rely on a traditional hierarchy for decision-making, simultaneously existing in a position of decision-making dissonance and empowerment, and (2) teacher leaders in an alternative setting focused on project-based learning were empowered to authentically use student voices to develop curriculum and school structures, causing internal conflict due to longstanding educational traditions and limited resources. While teachers felt liberated beyond the classroom to lead, they simultaneously felt overwhelmed by the demands of teaching and leading. They recognized that they needed decision-making and conflict-resolution structures to more effectively navigate the liminal space of teacher and leader. The implications for those engaging in democratic structures for schools need processes and protocols for decision-making and conflict resolution.
Keywords: Teacher Leadership; Teacher-Led Schools; Non-hierarchical leadership structures; Community Learning Exchanges; Teachers--Attitudes; Educational leadership; Nepantla; Alternative schools; Student participation in curriculum planning; Teaching, Freedom of